The role of Plagiomniaceae in forming moss cover in the Ukrainian Forest-Steppe (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The characteristics of bryocoenoses with Plagiomniaceae is given with showing the phytocoenotic role of this family. Phytocoenotic tables of the association Plagiomnio cuspidati- Homalietum trichomanoidis (Pec. 1965) Marst. 1993 and outrank community of Plagiomnium cuspidatum – comm. are given.
Keywords: mosses, Plagiomniaceae, Ukrainian Forest-Steppe, briocommunity, briocoenose, syntacson.